2012
DOI: 10.1128/jvi.01210-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MW Polyomavirus, a Novel Polyomavirus in Human Stool

Abstract: We have discovered a novel polyomavirus present in multiple human stool samples. The virus was initially identified by shotgun pyrosequencing of DNA purified from virus-like particles isolated from a stool sample collected from a healthy child from Malawi. We subsequently sequenced the virus' 4,927-bp genome, which has been provisionally named MW polyomavirus (MWPyV). The virus has genomic features characteristic of the family Polyomaviridae but is highly divergent from other members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 47 publications
1
152
1
7
Order By: Relevance
“…Polyomaviruses and adenoviruses were also relatively common. We detected polyomaviruses MWPyV [9], Merkel Cell [10,11], human polyomavirus (HPyV)-6, HPyV7 [12], and JC [13]. The anelloviruses were found in all of the body sites except stool.…”
Section: Resultsmentioning
confidence: 97%
“…Polyomaviruses and adenoviruses were also relatively common. We detected polyomaviruses MWPyV [9], Merkel Cell [10,11], human polyomavirus (HPyV)-6, HPyV7 [12], and JC [13]. The anelloviruses were found in all of the body sites except stool.…”
Section: Resultsmentioning
confidence: 97%
“…Both HPyV6 and HPyV7 have been detected in urine, feces, and nasopharyngeal swabs in transplant recipients (Siebrasse et al 2012). Their relationships with a disease in immunosuppression or in malignant transformations have recently been indicated in few studies (Schrama et al 2014;Ho et al 2015).…”
Section: Hpyv6 and Hpyv7mentioning
confidence: 99%
“…MWPyV was isolated from a stool sample of a healthy child from Malawi (Siebrasse et al 2012). In another study, Buck et al identified a virus in a specimen from a patient with warts, hypogammaglobulinemia, infections, and myelokathexis syndrome; the virus was named HPyV10 and showed 95%-99% similarity with MWPyV, suggesting that they were the same virus .…”
Section: Mwpyvmentioning
confidence: 99%
See 1 more Smart Citation
“…The human polyomaviruses JCPyV (2) and BKPyV (3) were discovered in 1971 and subsequently shown to be associated with progressive multifocal leukoencephalopathy and polyomavirus-associated nephropathy, respectively. Remarkably, 10 new human polyomaviruses have been identified in the last 6 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). One of these, Merkel cell polyomavirus (MCPyV), is the causative agent of Merkel cell carcinoma, a rare neuroendocrine tumor of the skin (6).…”
mentioning
confidence: 99%